Pengaruh Keterlibatan Pemakai Dalam Pengembangan Sistem Informasi, Kemampuan Teknik Personal, Dukungan Manajemen Puncak, Pelatihan Dan Pendidikan Terhadap Kinerja Sistem Informasi Akuntansi Pada LPD Di Kecamatan Abiansemal - Witara I Gede Suet Sutra; Sumadi Ni Komang (Hita Akuntansi dan Keuangan, 2022)
An accounting information system is a system that processes data and transactions to produce useful information for planning, controlling, and operating a business. Factors that affect the performance of SIA such as user involvement in the development of information systems, personal technical skills, top management support, training and education. This research is in the form of associative using a questionnaire. The number of samples studied as many as 117 respondents using purposive sampling technique of determining the sample using criteria. The results of hypothesis testing indicate that the variables of user involvement in information system development, personal technical skills, top management support, training and education affect the performance of SIA at LPD in Abiansemal District